The field of wacky inventions - Carman, Patrick (Carman, Patrick. Floors novel, 2013)
Leo and Remi have gotten used to the strangeness of the Whippet Hotel, but when the entire top floor is hoisted into the sky and transported to the field of wacky inventions, they find that they must compete against a number of foes to solve a puzzle or lose their beloved hotel forever.